1996
DOI: 10.1128/iai.64.8.2904-2910.1996
|View full text |Cite
|
Sign up to set email alerts
|

The major surface protein complex of Treponema denticola depolarizes and induces ion channels in HeLa cell membranes

Abstract: The oral spirochete Treponema denticola is closely associated with periodontal diseases in humans. The 53-kDa major surface protein (Msp) located in the outer membrane of T. denticola serovar a (ATCC 35405) has both pore-forming activity and adhesin activity. We have used standard patch clamp recording methods to study the effects of a partially purified outer membrane complex containing Msp on HeLa cells. The Msp complex was free of the chymotrypsin-like proteinase also found in the outer membrane of T. denti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 55 publications
(64 reference statements)
4
72
0
Order By: Relevance
“…The electron micrographs clearly indicate that MspA is a major protein of the outer sheath, supporting our previous results from subcellular fractionation, SDS-PAGE analysis and deter-gent treatment of the outer membrane [8]. The T. denticola Msp protein was shown to be an outer membrane porin, with binding properties to host cell surface proteins [4,5,12]. Further it was reported that the Msp protein forms a hexagonal array in the outer sheath [4], however, this could not be con¢rmed by a recent publication [2].…”
Section: Generation Of a Mspa Speci¢c Antiserum Andsupporting
confidence: 86%
“…The electron micrographs clearly indicate that MspA is a major protein of the outer sheath, supporting our previous results from subcellular fractionation, SDS-PAGE analysis and deter-gent treatment of the outer membrane [8]. The T. denticola Msp protein was shown to be an outer membrane porin, with binding properties to host cell surface proteins [4,5,12]. Further it was reported that the Msp protein forms a hexagonal array in the outer sheath [4], however, this could not be con¢rmed by a recent publication [2].…”
Section: Generation Of a Mspa Speci¢c Antiserum Andsupporting
confidence: 86%
“…Like most bacterial outer membrane porins, Msp was relatively resistant to proteolytic degradation. This resistance to endogenous proteases was employed in a recent study as a means of puri¢cation of Msp from crude outer membrane extracts [6]. Msp may play a role in presentation of CTLP on the cell surface, thus protecting the cell from its degradative e¡ects.…”
Section: Resultsmentioning
confidence: 99%
“…Two prominent surface antigens of T. denticola ATCC 35405, the poreforming major surface protein (Msp) and the chymotrypsin-like protease (CTLP), adhered to and were cytotoxic to epithelial cells [5]. Msp induced pore formation in HeLa cell membranes [6]. CTLP activ-ity was required for T. denticola migration through a basement membrane model [7].…”
Section: Introductionmentioning
confidence: 99%
“…Msp is part of an outer sheath complex in T. denticola; it has both adhesin and porin properties [67,70,71]. Msp is also found in T. vincentii, but not in other oral spirochaetes [72,73].…”
Section: Adhesion and Proteolytic Mechanisms Of Oral Treponemesmentioning
confidence: 99%